Pengaruh kurs, inflasi, PDB dan harga karet internasional terhadap ekspor karet Indonesia Ke Tiongkok dan Amerika Serikat - Fihri, Faisal; Haryadi, Haryadi; Nurhayani, Nurhayani (Prodi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2021)
This study aims to: 1) calculate and analyze the development of exchange rates, inflation, GDP, international rubber prices, and Indonesian rubber exports to China and the United States. 2) To determine the income contribution of women workers in Talang Village, 3). To calculate and analyze the factors that affect the export of Indonesian rubber to China and the United States. The analytical method used is descriptive quantitative using multiple linear regression analysis. The results show that the exchange rate development fluctuated from 2001 to 2019, with an average exchange rate development from 2001 to 2019 of 3.13 percent. Then the average general annual inflation of Indonesia for 19 years with inflation developments that occur up and down or fluctuate. The average growth of rubber prices is 9.24 percent. Furthermore, the volume of rubber exports to China in 2001-2019 tends to decrease. The average development of rubber export volume to China in 2001-2019 was -1.95 percent. Meanwhile, the development of rubber export volume to America in 2001-2019 tends to increase. The average growth of rubber export volume to China in 2001-2019 was 1.34 percent. Based on the results of multiple linear regression, the importance of rubber exports to China is influenced by the variables of the exchange rate, GDP, and rubber prices. Meanwhile, the rubber price variable only affects the volume of rubber exports to America. Â Keywords: Export of rubber, Exchange rate, Inflation, GDP, Rubber price